Site-specific nutrient management under conservation agriculture-based spring wheat in Trans-Gangetic Plains of India - HASANAIN, MOHAMMAD; SINGH, V K; RATHORE, S S; SHEKHAWAT, KAPILA; SINGH, R K; DWIVEDI, B S; BHATIA, ARTI; UPADYAYA, P K (The Indian Journal of Agricultural Sciences, 2021)
The experiment was conducted during 2018-19 and 2019-20 at ICAR-IARI research farm, to see the effect of crop establishment and nutrient management options on growth and yield of wheat under maize-wheat system. The experiment was laid out in split plot design with 03 replications, comprising conventional tillage without residue (CT-R), conventional tillage with 3 t/ha residue (CT+R), permanent raised bed without residue (PRB-R) and permanent raised bed with 3 t/ha residue (PRB+R) in main plot and nutrient management, viz. soil test-based(STB), Nutrient Expert® based (NE) and NE+ GreenSeekerTM based recommendations (NE+GS) in sub-plot. A significantly (P≤0.05) higher crop growth, viz. plant height, dry matter accumulation and leaf area index under PRB+R compared to other crop establishment technique. Differentyield parameters (yield, grain straw ratio and harvest index) and yield attributes of wheat grown under PRB+R were significantly higher (P≤0.05) over other crop establishment technique. A significantly (P≤0.05) higher crop growth, yield attributes, grain yield (5.01 and 5.05 t/ha), grain: straw ratio (0.65 and 0.65) and harvest index (39.31 and 39.36) of wheat were recorded with NE+GS based fertilization during 2018-19 and 2019- 20, respectively. Pearson correlation matrix analyzed for different growth and yield parameters showed a significant positive correlation (r) among themselves. Study infer that growing of wheat on the permanent raised bed along with 03 t/ha residue retention on surface and precision nutrient prescription using NE and GreenSeekerTM optical sensor showed promise for sustainable high productivity in intensively cultivated Trans-Gangetic Plains.